Susceptibility of different chicken lines to H7N1 highly pathogenic avian influenza virus and the role of Mx gene polymorphism coding amino acid position 631 - Sironi, L.; Williams, J.L.; Moreno Martin, A.M.; Ramelli, P.; Stella, A.; Weigend, S.; Lombardi, G.; Cordioli, P.; Mariani, P.; Han Jianlin (Elsevier, 2008)
Five chicken lines were experimentally infected with a HPAI H7N1 virus, to examine the variation in susceptibility to infection. Three lines showed high susceptibility to the virus, while two showed some resistance, with 7 out of 20, and 11 out of 15 birds, respectively, remaining healthy and surviving the experimental infection. Genotyping for the G/A polymorphism at position 2032 of Mx cDNA showed that one line was fixed for the G allele, and two were segregating for A and G alleles. Birds in the other two lines were selected to be fixed for the A allele. Statistical analyses indicated that the Mx genotype did not affect the clinical status or the time course of infection after viral inoculation.